2014
DOI: 10.1007/s12098-014-1523-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Dengue Among Children According to Revised WHO Classification: Analysis of a 2012 Outbreak from Southern India

Abstract: Children between 5 and 15 y were most affected by dengue fever. Pain abdomen and vomiting were most common presenting symptoms. Ascites, plerural effusion, hepatomegaly, gall bladder wall thickening and abnormal LFT were found significantly high in severe dengue cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

24
38
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 13 publications
24
38
0
4
Order By: Relevance
“…Only one prior study reported abdominal pain as common presenting complaint, thus there should be a high index of suspicion in children presenting with fever and abdominal pain especially during the outbreak of dengue. 7 Lethargy was present in 72% of children and was the only single parameter associated with poor outcome (p < 0.005).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only one prior study reported abdominal pain as common presenting complaint, thus there should be a high index of suspicion in children presenting with fever and abdominal pain especially during the outbreak of dengue. 7 Lethargy was present in 72% of children and was the only single parameter associated with poor outcome (p < 0.005).…”
Section: Resultsmentioning
confidence: 99%
“…This study also had a male preponderence of 62% and mean age was 8 years which is similar to the other Indian studies. 7,8 The most common presenting symptom was lethargy, abdominal pain and mucosal bleeds, fever was present universally in all patients. Only one prior study reported abdominal pain as common presenting complaint, thus there should be a high index of suspicion in children presenting with fever and abdominal pain especially during the outbreak of dengue.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations